STUDY KINETIC PYROLYSIS OF ULIN WOOD POWDER USING THERMOGRAVIMETRIC ANALYSIS - Adha, Dhea Nur; Subagyono, R.R. Dirgarini; Gunawan, Rahmat (PROSIDING SEMINAR KIMIA, 2023)
A kinetic study of ironwood powder pyrolysis using thermogravimetric analysis has been conducted. This study aims to determine the thermal decomposition process and determine the activation energy value of ironwood powder pyrolysis using the free Kissinger-Akahira-Sunose (KAS) and Friedman models. Pyrolysis in this study used heating rates of 10, 15, 20, and 25 ºC/minute. The active temperature range of ironwood powder pyrolysis was 130.88 – 552.21ºC. The thermal decomposition process occurred in three stages, namely 1. evaporation of water or moisture, 2. active pyrolysis for the decomposition of hemicellulose, cellulose and lignin compounds, and 3. passive pyrolysis caused by gasification and the formation of non-volatile carbon compounds which evaporate to form CO and CO2 gases at high temperatures. The average activation energy of the pyrolysis of ironwood powder using the Kissinger-Akahira-Sunose (KAS) and Friedman methods were 137.34 ± 30.05 kJ/mol and 147.83 ± 36.66 kJ/mol, respectively. Keywords: Kinetic Study, Iron Wood Powder, Thermogravimetric Analysis